2004
DOI: 10.1021/ma0400416
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Induced Crystallization in Poly(ethylene terephthalate) during Mass Transport:  Mechanism and Boundary Condition

Abstract: The mechanism of mass transport and the related crystallization in poly(ethylene terephthalate) (PET) were studied. Solvent-induced crystallization can occur during the transport process in PET at low temperature. The important effect of changing the surrounding medium to solvent molecules is to reduce the glass transition temperature. This phenomenon is called “plasticization”. The extent of plasticization relies on the amount of solvent around the polymer molecules, i.e., the concentration of solvent which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…A relationship between conducting time (square root of the time) and crystallization front (length from edge of the specimen to crystallization front) is shown in Figure 6. The plot clears that diffusion distance of acetone is in proportion to square root of the exposed time, indicating the diffusion of acetone vapor in PLA obeys Fick type diffusion [30][31][32]. These results show good agreement with the results of the PLA crystallization immersed in acetone solvent.…”
Section: Crystallization Behavior Of Amorphous Pla By Acetone Vaporsupporting
confidence: 78%
“…A relationship between conducting time (square root of the time) and crystallization front (length from edge of the specimen to crystallization front) is shown in Figure 6. The plot clears that diffusion distance of acetone is in proportion to square root of the exposed time, indicating the diffusion of acetone vapor in PLA obeys Fick type diffusion [30][31][32]. These results show good agreement with the results of the PLA crystallization immersed in acetone solvent.…”
Section: Crystallization Behavior Of Amorphous Pla By Acetone Vaporsupporting
confidence: 78%
“…The plot clears that permeation distance of acetone is in proportion to square root of the immersion time, indicating that the permeation obeys Fick type diffusion. [33][34][35] The same experiment was conducted at 40 C and 50 C, and the results are plotted in Figure 3. The rate of the permeation of acetone increased with increasing of the conducted temperature.…”
Section: Crystallization Behavior Of Amorphous Plamentioning
confidence: 99%
“…Permeation of acetone into the amorphous phase of PET promoted the crystallization of PET. [33][34][35] We applied the crystallization method to PLA and found that the crystallization was induced by some organic solvents, especially acetone. In this article, we investigated the solvent induced crystallization of amorphous PLA and its properties precisely, and found out that the acetone not only induced crystallization but also played a role of a plasticizer…”
Section: Introductionmentioning
confidence: 99%
“…Organic solvent can induce crystallization in PET polymer at low temperature by plasticizing effect. The extent of plasticization depends on the amount of solvent that has penetrated inside the polymer [2,4]. Some papers have reported that amorphous PET can be crystallized by immersion in selected organic solvents (i.e.…”
Section: Introductionmentioning
confidence: 99%